LEGALITAS HUKUM PERKAWINAN BEDA AGAMA DALAM PRAKTIK HUKUM MASYARAKAT INDONESIA: HARMONISASI HUKUM POSITIF DAN HUKUM AGAMA - Najiburrahman, Najiburrahman; Marzuki, Ismail; Layyinah, Qurratul (JURNAL HAKAM, 2024)
The right to marry and choose one's spouse freely is part of human rights, including marriages performed by interfaith couples. The problem with interfaith marriage, however, lies in the restrictive positive legal norms that accommodate religious norms. The purpose of this research is to examine the mechanism, norms, and legal basis of interfaith marriage, as well as its practice in Indonesia. While the research method used in this research is the normative juridical research method with various approaches, including the statutory approach, conceptual approach, and case approach, which is further supported by an analysis of concrete evidence of the practice of interfaith marriage based on court jurisprudence. The results of the study show that although some interfaith couples can carry out their marriages with a variety of certain mechanisms that are quite strict, this still shows the weak harmonization of positive law and religious law in the practice of interfaith marriages in Indonesia. The norms and legal bases referred to by interfaith marriage partners, such as Article 35 of Law No. 23/2006 and Article 10 of Law No. 39/1999, in practice still face various social and administrative challenges. Similarly, the court jurisprudence that is often used as a benchmark in the implementation of interfaith marriage has not been able to create legal certainty that is universally just, given its casuistic nature.Keywords: Harmonization of positive law and religious law; legality of law; interfaith marriage; and legal practices of Indonesian society.